KAJIAN TERHADAP TOLAK UKUR KINERJA PEGAWAI NEGERI SIPIL DAERAH DALAM KENAIKAN PANGKAT DAN JABATAN DI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN KLUNGKUNG - Risca Yuni Arta, Ni Putu; R., Ibrahim; Suardita, I Ketut (Kertha Wicara : Journal Ilmu Hukum, 2013)
A civil servant has a standardization in the case of promotion of rank and position . Thehigher the rank and position of a person, the wider the authority is. It requires a competency ofhuman resources. It can be seen by how the perfomance of a civil servant when doing a job. Theexistence of excess of tolerance makes the performance assessment becoming not optimum andraises a negative impression in the society. The formulation of the problem that can be taken isthat what to be the benchmark for the promotion of rank and position of a civil servant and whatviolation to happen related with the rank and position. The type of research used in thisdiscussion is an empiric research with the case approach. So that the conclusion obtained is thatthe benchmark for the promotion of rank and position is a credibility, creativity, inovation and theexistence of potential. The lack of responsibility while doing a job causing the abuse of authorityso that resulted in smearing of reputation of the institution and individual. So that the transparentassessment is required for the establishment of a competent human resources in its field.
Keywords: Civil Servant, The Promotion of Rank, Basic of Assessment, Performance